2014
DOI: 10.1002/j.2161-0029.2014.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Counseling Students' Decision to Pursue a Gerocounseling Specialization

Abstract: The authors examined which variables predicted the likelihood of counseling students' decision to pursue a gerocounseling specialization by using logistic regression analysis. Results found that overall interest, perceived preparation, training willingness, and importance were predictive factors. Curriculum strategies on how to implement these variables into existing counselor education course work are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Despite elimination of the NCGC certification and the GC track, researchers have found that counseling students still possess a relatively high interest in working with clients on common aging‐related issues, such as grief, caregiving, retirement, and intergenerational family issues (Foster et al, 2009, 2014). Moreover, 19% to 35% of students surveyed expressed interest in working in settings such as a hospital geriatric unit, hospice, or even a nursing home (Foster et al, 2009).…”
Section: Gerontological Counseling: History and Professional Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite elimination of the NCGC certification and the GC track, researchers have found that counseling students still possess a relatively high interest in working with clients on common aging‐related issues, such as grief, caregiving, retirement, and intergenerational family issues (Foster et al, 2009, 2014). Moreover, 19% to 35% of students surveyed expressed interest in working in settings such as a hospital geriatric unit, hospice, or even a nursing home (Foster et al, 2009).…”
Section: Gerontological Counseling: History and Professional Statusmentioning
confidence: 99%
“…The counseling profession places a premium on promoting human development (Kaplan, Tarvydas, & Gladding, 2014) through practices that are undergirded by wellness (Myers & Sweeney, 2008), strengths‐based perspectives (Vereen, Hill, Sosa, & Kress, 2014), multiculturalism, and social justice (Ratts, Singh, Nassar‐McMillan, Butler, & McCullough, 2016). Integral to counselor professional identity is the belief that promoting these values can and should occur across the life span (Myers & Harper, 2004), and authors have argued for an expansion of professional resources that promote work with older adults and aging communities (Foster, Evans, & Chew, 2014; Fullen, 2018). Historically, expanding the profession’s scope of practice to include older adults has served as a driver for the development of competencies and standards (e.g., Myers, 1995; Myers & Schwiebert, 1996), as well as attempts to promote specialty certification through entities such as the National Board for Certified Counselors (NBCC), the American Mental Health Counselors Association, and the Council for Accreditation of Counseling and Related Educational Programs (CACREP).…”
mentioning
confidence: 99%
“…Researchers have demonstrated that counselors often overlook mental health symptoms, such as dementia, depression, or suicide, within the older population (Foster et al, ). Older adults have higher rates of receiving a diagnosis of dementia and experiencing symptoms such as memory loss; language disruption; agitation; and personality, emotional, and behavior changes (Abraham, ).…”
Section: Discussionmentioning
confidence: 99%
“…Counseling practices associated with older adults relate to a significant gap considering the recency of the baby boomer generation and of generational cohorts living longer (Foster, Evans, & Chew, ; Kepic et al, ). Researchers have also alluded to the growing disparities in counselor education, supervision, and training for addressing factors of wellness and development among older adults (Fullen, ).…”
Section: In‐home Counseling and Ecological Systems Theorymentioning
confidence: 99%
“…The counseling profession has established a need for research and best practices for counseling older adults because of its emphasis on development across the life span (Kampfe, 2015;Myers & Harper, 2004), student and professional interest in gerontology (Foster et al, 2009(Foster et al, , 2014Fowler & Hoquee, 2016;Wagner et al, 2019), and legislative advocacy opportunities (Bergman, 2013). With Medicare reimbursement for counselors as a primary focus of legislative advocacy efforts (Field, 2017;Fullen, 2016), there is a need to legitimize gerontological counseling (GC) as a credible area of competency for counseling professionals, both as an avenue for improving client care across the life span and as proof that the counseling profession possesses relevant educational and training competencies to substantiate inclusion of counselors as Medicare-eligible providers (Bergman, 2013).…”
mentioning
confidence: 99%